2014
DOI: 10.1007/jhep12(2014)117
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of spontaneously broken supersymmetry on an anti-D3-brane in KKLT dS vacua

Abstract: The KKLT construction of de Sitter vacua includes an uplifting term coming from an anti-D3-brane. Here we show how this term can arise via spontaneous breaking of supersymmetry, based on the emergence of a nilpotent chiral supermultiplet on the worldvolume of the anti-D3-brane. We establish and use the fact that both the DBI as well as the WZ term, with account of orientifolding, acquire a form of the Volkov-Akulov action. For an O3 orientifold involution of R 9,1 we demonstrate the cancellation between the fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
268
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 141 publications
(279 citation statements)
references
References 45 publications
(156 reference statements)
8
268
0
Order By: Relevance
“…Note that at the minimum ϕ = 0, the axion mass squared becomes 4W 2 0 = 4m 2 3/2 . If we take a more general function 16) and the potential is…”
Section: E-modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that at the minimum ϕ = 0, the axion mass squared becomes 4W 2 0 = 4m 2 3/2 . If we take a more general function 16) and the potential is…”
Section: E-modelsmentioning
confidence: 99%
“…Its worldvolume theory includes a Volkov-Akulov fermion goldstino [3,4], which can be equivalently described in terms of a nilpotent scalar superfield S with S 2 (x, θ) = 0 [5][6][7][8][9][10][11][12][13][14][15]. This nilpotent superfield allows for a manifestly supersymmetric description of the uplift to a de Sitter minimum [16][17][18][19][20][21][22][23]. In a parallel development, it has been realized that nilpotent superfields have great potential as a model building tool in effective supergravity theories of inflation [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…These actions after gauge-fixing of the local fermionic κ-symmetry have spontaneously broken supersymmetry in the presence of the fermions remaining on the brane after the gauge-fixing. The corresponding analysis of the actions was performed in [3] in a flat supergravity background. 1 It was shown that in the presence of fermions, under certain orientifolding conditions, the cancelation of the DBI and WZ terms on the D3 brane and doubling on the D3 take place in the exact nonlinear expression with fermions.…”
Section: Jhep05(2015)058mentioning
confidence: 99%
“…The fermion action is a Volkov-Akulov goldstino action [16,17], as expected according to [11], in a flat background. The result of [3] is…”
Section: Jhep05(2015)058mentioning
confidence: 99%
See 1 more Smart Citation